Development of Playing Card Learning Media Using Team Games Tournament Model on Volleyball Passing Materials in Grade 5 of Elementary School - Iswahyudi, Suhud; Leksono, Ibud Priono; Rusmawati, Retno Danu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2022)
The This research aims to develop a learning media with the teams games tournament (TGT) model using playing cards as a medium in the learning of Sports and Health Physical Education (SHPE) with volleyball game passing materials in elementary school. This research is research and development (R&D) by adopting the 4D development model (Define, Design, Development, and Dissemination) proposed by Thiagarajan in 1974. This study was conducted in the 5th grade of public elementary school, Lamongan, East Java. The data collection technique in this study is in the form of validity questionnaires and practicality of teacher response and student response given to media experts, material experts, teachers and students. The data analysis technique used in this study is to calculate the average percentage score that can be seen from the results of media and material validation and the practical results of teacher and student responses. Results obtained from the media validity test showed that playing card learning using the TGT model on 5th grade volleyball passing material got a very valid category with a percentage score of 90.28%. Practicality got a very practical category with a percentage score of 94.89%. Playing card learning using the TGT model on 5th grade of volleyball passing material is said to be valid and practical because it has met the assessment criteria seen from the media presentation, aspects of media content, aspects of image illustration, material aspects as well as the response of teachers and students. This shows that playing card learning using the TGT model on 5th grade elementary school volleyball passing material is feasible for the use by teachers and students in the SHPE learning process. This research is expected to help educators in using learning media in elementary schools, especially SHPE subjects of volleyball passing materials and can be a reference for researchers who will carry out research with the same study in elementary school.